If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(6x-9)-1=4x-5
We move all terms to the left:
(6x-9)-1-(4x-5)=0
We get rid of parentheses
6x-4x-9+5-1=0
We add all the numbers together, and all the variables
2x-5=0
We move all terms containing x to the left, all other terms to the right
2x=5
x=5/2
x=2+1/2
| 1/2(x-3)+3/4(x+2)=x-1 | | 5x/2+100=x | | x2+1/3x+1/36=7/36 | | -1=x-4.2/x-1.3 | | s6-26=118 | | 7/2x+1-3=2/2x+1 | | t=21-9 | | 6(x+16)=132 | | 5(n-11)=35 | | x4+6x3+9x-12=0 | | 5(m-8)=75 | | 4(x+1)=3x+16 | | 5/x-3+2=1/x-3 | | 3(p+7)=45 | | Z=4-1j+2+7j | | Z=4-1j+2+7j5 | | 4x/9=14 | | 10x/7=250 | | -9/4x-5=2/3x | | 4n-6=13 | | 8x+10=12-3x | | 6x-25=7x+10 | | 45-x=120 | | 34+56+x=76 | | 8+a+12=3a | | 4(3x-2=28 | | 5x+0.5=0.5 | | A=7/5(h-92) | | P+20=5p | | 8x-24=5x+17 | | 2(x-8)(x-3)=0 | | 8(x-5)=2x |